Femoroacetabular impingement syndrome - Tolga Ege; Nuray Can; Omer Ersen; Selim Turkkan; Ibrahim Yanmis (Archives of Clinical and Experimental Surgery, 2016)
Femoroacetabular impingement (FAI) syndrome is a recently understood hip condition that describes the pathologic contact between the femoral neck and the acetabular rim. Previously, it was also called and ldquo;acetabular rim syndrome and rdquo; or and ldquo;cervicoacetabular impingement syndrome and rdquo;. It is characterized by a developmental disorder affecting the femoral neck, acetabular rim and labrum. The chronic irritation on the hip joint causes chondral damage and mechanical changes, and these degenerative changes eventually lead to osteoarthritis. Two types of FAI have been described: Cam type and pincer type. Treatment options for FAI are conservative, open, mini open and arthroscopic surgery. [Arch Clin Exp Surg 2016; 5(1.000): 42-47]